The 8th Annual IEEE International Conference on Nano/Micro Engineered and Molecular Systems 2013
DOI: 10.1109/nems.2013.6559947
|View full text |Cite
|
Sign up to set email alerts
|

Weak light characteristics of a new photoelectric sensor with potential biosensor application

Abstract: Keywords -weak light detection, biosensor, semiconductor quantum dot;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…3 a shows an LCD screen, a micro controller unit (MCU) and another processing unit in three layers. This layered configuration decreased the size of the data processing unit to 9.6 × 6.3 × 3.5 cm, only half the size of a previous planar layout of our data processing unit [15].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…3 a shows an LCD screen, a micro controller unit (MCU) and another processing unit in three layers. This layered configuration decreased the size of the data processing unit to 9.6 × 6.3 × 3.5 cm, only half the size of a previous planar layout of our data processing unit [15].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Studies have shown that with a layer of QDs of resonant tunnelling diodes and field-effect transistors it is possible to detect single photon at a temperature of 77 k [1][2][3][4]. The detectors were used for sensing the electrostatic potential of the individual photo-induced carriers that were trapped in the QDs.…”
mentioning
confidence: 99%